PARTISIPASI MASYARAKAT PETANI DALAM MENDUKUNG PROGRAM PENGEMBANGAN LUMBUNG PANGAN MASYARAKAT (LPM) DI DESA MANURARA KECAMATAN KATIKU TANA SELATAN KABUPATEN SUMBA TENGAH - Hendrikus Lepa Sabaora; Johanna Suek; Made Tusan Surayasa (Buletin Ilmiah Impas, 2021)
Participation studies are important because they determine the success of the program. When community participation is high, the food granary program will be successful and conversely low participation will make the food granary program fail to run. The research aims to examine the level of participation of the farming community in supporting the Community Food Granary Development Program. This study determines the closeness of the relationship between social and economic factors and community participation. Participation is measured based on the activities of the food barn from four (4) stages, namely; The planning, implementation, evaluation and results utilization stages. Participation is measured using a Likert scale with categories very high, high, medium and low. The closeness of the relationship between socio-economic variables and participation was analyzed using Rank Spearman analysis. The results of the study showed that community participation is classified as moderate with a score of 3982 (61.60%). The closeness of the relationship between socio-economic factors, namely age0.391 (moderate), amount of production of 0.409 (moderate) and type of workof 0.620 (strong)has a significant relationship with participation. While, the formal education factor does not significant relationship to participation with a correlation coefficient of 0.150 (weak).